An analysis of export performance of major spices of India in the globalized regime - Ramannagol, Shilpa K.; Nagoor, B. H. (Journal of Plantation Crops, 2025)
Spices of India hold significant economic importance due to its contribution to exports, providing livelihood for millions of people and being net foreign exchange earner. In the era of globalisation, countries of the world are integrating through trade and investment. The Indian spices exports are facing international competition after liberalizing its trade as part of New Economic Policy of 1991. In this regard, the present study analysis the export performance of Indian Spices since 1991. Comparison is also made with period prior to trade liberalisation. Multiple regression analysis is applied to quantify and analyse the export performance of Spices. The results of multiple regression shows that cumin and chilli exports during the pre-globalization period were not highly responsive to economic variables, as government interventions and domestic consumption patterns limited the influence of global market forces. Unlike the pre-globalization period, where trade restrictions limited the impact of economic factors, exchange rate fluctuations, emerged as a key determinant of cumin and chilli exports in the liberalized era. Further the findings indicate that, in the post-globalization era, spice exports have become more responsive to global economic trends, with exchange rate movements, international demand, and price dynamics playing a crucial role in shaping India's competitive position in the global spice trade.